2007
DOI: 10.1162/ling.2007.38.1.1
|View full text |Cite
|
Sign up to set email alerts
|

V-Raising and Grammar Competition in Korean: Evidence from Negation and Quantifier Scope

Abstract: In a head-final language, V-raising is hard to detect since there is no evidence from the string to support a raising analysis. If the language has a cliticlike negation that associates with the verb in syntax, then scope facts concerning negation and a quantified object NP could provide evidence regarding the height of the verb. Even so, such facts are rare, especially in the input to children, and so we might expect that not all speakers exposed to a head-final language acquire the same grammar as far as V-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 18 publications
3
68
1
Order By: Relevance
“…6, we showed that many of the alternative tests proposed for identifying the verb position in Korean (10)(11)(12)(13) are in fact consistent with both verb-raising and tense-lowering analyses. In contrast, the scope of negation and object quantified phrases (QPs) is a good diagnostic of the position of the verb in a Korean speaker's representation of clause structure.…”
Section: Significancementioning
confidence: 53%
See 4 more Smart Citations
“…6, we showed that many of the alternative tests proposed for identifying the verb position in Korean (10)(11)(12)(13) are in fact consistent with both verb-raising and tense-lowering analyses. In contrast, the scope of negation and object quantified phrases (QPs) is a good diagnostic of the position of the verb in a Korean speaker's representation of clause structure.…”
Section: Significancementioning
confidence: 53%
“…The study reported in ref. 6 showed roughly the same size split in the population for both long and short negation, but it was a between-subjects study and as such does not tell us whether any given individual would show the same pattern for both types of negation. Second, speakers should show the same pattern of behavior over time.…”
Section: Significancementioning
confidence: 84%
See 3 more Smart Citations